Aksiologi Ilmu: Relasi Ilmu dan Etika - Imas Masruroh; Nanat Fatah Natsir; Erni Haryanti (Peneliti.net, 2021)
Axiology is a branch of philosophy that deals with values. The term axiology comes from the words axios and logos. The existence of science in this world is nothing but to help humans achieve their goals. Practically offers convenience in various areas of life. Meanwhile, ethics can be translated as values ​​or moral norms that guide a person or a group in regulating their behavior. The purpose of this study is to analyze the relationship between science and ethics. The research method used is literature study. The results of the study show that science is associated with values ​​/ ethics / morals, then science is not value-free, meaning that the development of science and technology must look at the ethical aspect, because if not then science will no longer help humans achieve goals but help humans create goals